PENERAPAN AGILE DEVELOPMENT METHODS PADA PERANCANGAN SISTEM INFORAMSI RENTAL MOBIL BAROKAH TRANS - Adi Susanto (Fakultas Sains dan Teknologi, Universitas Ibrahimy, 2023)
The existence of transportation as a very important means in everyday life to facilitate mobility and efficiency when moving from one place to another. Car rental is an alternative choice for the community by providing rental vehicles for a certain period of time. Customers or the public can rent a car for tourist trips, business needs, or to be used as a replacement vehicle if the private vehicle is under repair. Barokah trans is one of the car rental business actors that serves the many needs for transportation at this time, a website-based information system is a solution amidst the difficulty for the public to get car rental information in cities that have never been visited and the flexibility in ordering a car without having to come in person to a car rental place to place an order. The application of agile development methods in the development of an information system becomes a structured guide by utilizing computer and internet technology to support car rental business processes. The information system built in the form of a website application with a centralized database offers speed in accessing, processing transaction data, ease of use, and flexibility in use that can be accessed anywhere.